FACTORS THAT INFLUENCING THE DIARRHEA EVENT IN SDN 2 BANJAREJO STUDENTS, PUDAK DISTRICT PONOROGO - Herdiana, Dyah; Setyo Budi Susanto; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2019)
Diarrhea is a disease that is still a public health problem in developing countries, including Indonesia. This is due to the high morbidity and mortality. The purpose of this study was to analyze the factors that influence the incidence of diarrhea in students at SDN 3 Banjarejo, Pudak District, Ponorogo Regency. The design of this research is analytic quantitative research with cross sectional approach, the focus of the research is to analyze the factors that influence the incidence of diarrhea in students at SDN 3 Banjarejo, Pudak District, Ponorogo Regency. The total sample of 44 respondents was taken with the Simple Random Sampling technique. The results showed that there were 18 respondents (40.9%) who had enough categories of hand washing. Most respondents have defecation behavior enough category as many as 21 respondents (47.7%). Most respondents have the behavior of consuming enough snacks as many as 21 respondents (47.7%). Most of the respondents had diarrhea as many as 26 respondents (59.1%). The results of the Linear Regression Test analysis showed a p-value of 0.009 <0.05 then H0 was rejected and H1 was accepted so it was concluded that there was a significant influence between hand washing behavior on the incidence of diarrhea in students at SDN 3 Banjarejo, Pudak District, Ponorogo Regency. It is expected that respondents like washing their hands with soap before and after doing anything, especially after touching poop, while also having to defecate in the toilet and eat healthy snacks by bringing supplies from home.